Conference Report: YEuCat Better Together – Collaborative Catalysis in a Changing World. Issue 15 (24th March 2022) - Mendes, Pedro S. F.; Vucetic, Nemanja; Valverde‐González, Antonio; Delporte, Maxime; Gonçalves, Liliana P. L.; Isapour, Ghodsieh; Khatamirad, Mohammad; Kinnaer, Marty; Lindenthal, Lorenz; Pointecouteau, Remy; Santos, A. Sofia G. G.; Schrenk, Florian; et al.
Abstract : "YEuCat Better Together was the first collaborative event organized by the Young European Catalysis Network with the goal of joining young minds to propose an innovative catalytic solution to a global problem." This and more about YEuCat Better Together can be found in this Guest Editorial.